Card Frauds and Customers’ Confidence in Alternative Banking Channels in Nigeria - Elumaro, Adegboyega J.; ObamuYI, Tomola M. (European Scientific Journal, ESJ, 2018)
The need to reduce banks’ operating costs and improve customer satisfaction has led to the deployment of Alternative Banking Channels (ABCs), through which banking transactions are performed. The Nigerian banking industry has aligned with this global trend leading to increased usage of ABCs by customers. However, fraudsters are taking advantage of this development to defraud unsuspecting customers resulting in customers’ loss of confidence. Arising from this problem, this paper investigated the effect of card frauds on customers’ confidence in ABCs in Nigeria. The study employed data obtained from Nigeria Deposit Insurance Corporation, Central Bank of Nigeria (CBN) and Nigerian Electronic Fraud Forum from 2012 to 2016. Various econometric analyses like Unit roots, co-integration test and Generalized Method of Moments were used to analyze the data. The Value of transactions on ABCs, proxied for customer confidence, was used as the dependent variable, while card frauds, proxied by value of frauds on Automated Teller Machines and Point of Sales (CPF), and web and online banking platforms (CNF) were included as independent variables. Banks’ Total Assets, Prime Lending rate and Inflation rate were included as control variables. The results showed negative relationship between card frauds and customer confidence in ABCs. The paper concluded that card frauds affect customer confidence in ABCs negatively leading to customers preferring inbranch transactions. The paper recommended improved collaborations between banks and CBN to tackle frauds and leverage on the Bank Verification Number platform to improve security of transactions on ABCs through biometric authentication.